Factors Associated With Dietary Quality During Initial and Later Stages of the COVID-19 Pandemic in Mexico - Batis, Carolina; Irizarry, Laura; Castellanos-Gutiérrez, Analí; Aburto, Tania C.; Rodríguez-Ramírez, Sonia; Stern, Dalia; Mejía, Carla; Bonvecchio, Anabelle (Frontiers in Nutrition, 2021)
Background: The COVID-19 pandemic disrupted the global economy and modified lifestyles. The aim of our study was to identify factors associated with dietary quality, and their frequency, in Mexican adults at the initial and later stages of the pandemic. Methods: Two online surveys were conducted between June and July 2020 (n=3,131) and between November and December 2020 (n=1,703 including non-participants from 1st round). A diet quality score was estimated using a short instrument to measure the consumption of several healthy/unhealthy food items. Linear regression models were used to identify the association between pandemic related factors and the diet quality score, adjusted by sociodemographic characteristics. The 2nd round was weighted to represent the 1st round. Results: During the 1st and 2nd rounds only ~12% of the sample perceived that their intake of healthy food decreased, relative to before the pandemic; ~20% perceived that their intake of unhealthy foods increased. Diet quality remained similar between the 1st and 2nd round. The following factors were negatively associated with diet quality: Eating food prepared away-from-home; going out to work ≥4 times/week; decreased time for food preparation; decreased interest in eating healthy; eating more due to anxiety, depression, or boredom; food insecurity; and stockpiling junk food. Purchasing food using a mixed modality of both in-store and home delivery was positively associated with diet quality. With the exception of eating more due to anxiety (reported by 47% of participants), all these factors were reported by a minority of participants during the first round (≤15%). During the 2nd round, there was an increase in the frequency of participants who reported eating food prepared away-from-home, going out to work ≥4 times/week, having less time to prepare food, being more interested in eating healthfully, and a decrease in participants eating more due to anxiety, depression or boredom, or stockpiling junk food. Conclusions: Most participants perceived that their dietary intake improved during both initial and later stages of the pandemic. This might be related to factors associated with higher dietary quality, such as not going out to work, eating homemade food, and online grocery shopping.